Gasohol Engine Performance with Various Ignition Timing - Hendry Y. Nanlohy; Suyatno Arief; Helen Riupassa; Martina Mini; Trismawati Trismawati; Mebin Samuel Panithasan (Universitas Negeri Malang, 2022)
Experimental research has been conducted on the effect of ignition timings on the characteristics and performance of gasohol engines such as power, torque, specific fuel consumption, and thermal efficiency. The fuel used in this research is pure gasoline and a mixture of 50% bioethanol (BE50). The results show that the ignition timing that gives the maximum effect occurs at the top and bottom dead points of 9 degrees for gasoline and 12 degrees for BE50 fuel. Furthermore, the maximum power is obtained at 6,500 rpm, and at an ignition time of 12 degrees BTDC the maximum power generated is 4.63 hp, while for an ignition time of 9 degrees BTDC the power generated is 3.38 hp which occurs at 6500 rpm. These results indicate that there is an increase in power of 6.4%. Moreover, the results also show that for optimal gasoline conditions, the amount of energy consumed at an engine speed of 7000 rpm is around 15705.78 kcal/hour, and for BE-50 it is around 12582.03 kcal/hour, where there is a reduction of about 25.44 %. However, in general, it can be seen that during optimal ignition, there is a saving in fuel consumption in the gasoline-BE50 mixture, while at the same time producing a fairly large thermal efficiency. These results indicate that BE50 has the potential to be used as an alternative fuel in small gasoline engines.